A Comparison of Domestic Demand and Export-led Growth Strategies for European Transition Economies: Dynamic Panel Data Analysis. Issue 3 (August 2018) - Sağlam, Yağmur; Egeli, Hüseyin Avni
The relationship between growth and trade has been argued many times in the literature. The topic is still current, dealing with different methodologies and countries by researchers. In this frame to understand the relationship theoretically and empirically better, the topic is examined again with a different approach which is explaining export-led growth (ELG) and domestic-demand-led growth (DLG) strategies comparatively for European transition economies. The annual data for the period between 1990 and 2015 were taken from Data Stream for 16 European (Central and Eastern Europe, Southeastern Europe and Balkans) transition economies and because data include both cross section and time dimension, it is necessary to apply dynamic panel data techniques. Second-generation unit root test (multifactor), Westerlund ECM panel co-integration test and heterogeneous panel causality test are applied, and long-term coefficients are estimated with common correlated effects (CCE) model. According to test results, not only ELG but also DLG strategy is accepted for European transition economies, and the direction of the relationship between growth and trade is bilateral. But the contribution of domestic demand on growth is seven times bigger than net export. The leading countries for ELG strategy are Romania, Bosnia and Herzegovina but for Poland and Czech Republic DLG strategy contributes more on economic growth. It is a better macroeconomic policy to have the balance between export-led and domestic-demand-led growth strategies for a sustainable economic growth. The key approach of high growth rate is to produce high technology with competitive price according to domestic demand and export it to the foreigner markets. JEL Codes: F14, C01, C33